The Role of Synthetic Data in Robotics: Accelerating Development and Innovation - Tanay Choudhary (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative role of synthetic data in modern robotics development and deployment. It examines how synthetic data addresses fundamental challenges in robotics by providing artificially generated datasets that mimic real-world scenarios. The article delves into the core advantages of synthetic data, including cost-effectiveness, scalability, and risk mitigation in robotic system development. It analyzes major tools and platforms used for synthetic data generation, with detailed discussions of CARLA, Gazebo, and Unreal Engine. The article addresses the critical challenge of the reality gap between simulated and real environments, exploring solutions through domain randomization and sim-to-real transfer techniques. It examines practical applications across autonomous driving, warehouse automation, and robotic surgery, demonstrating synthetic data’s impact on these domains. Furthermore, the article investigates future directions, including integration with generative AI, automated scenario generation, and collaborative simulation environments, providing insights into how synthetic data continues to evolve and shape the future of robotics development.